Projections of the Diencephalospinal Dopaminergic System to Peripheral Sense Organs in Larval Zebrafish (Danio rerio) - Haehnel-Taguchi, Melanie; Fernandes, António M.; Böhler, Margit; Schmitt, Ina; Tittel, Lena; Driever, Wolfgang (Frontiers in Neuroanatomy, 2018)
Dopaminergic neurons of the descending diencephalospinal system are located in the posterior tuberculum (PT) in zebrafish (Danio rerio), and correspond in mammals to the A11 group in hypothalamus and thalamus. In the larval zebrafish, they are likely the only source of central dopaminergic projections to the periphery. Here, we characterized posterior tubercular dopaminergic fibers projecting to peripheral sense organs, with a focus on the lateral line neuromasts. We labeled and identified catecholaminergic neurons and their projections by combining two immunofluorescence techniques, (i) using an antibody against Tyrosine hydroxylase, and (ii) using an antibody against GFP in transgenic zebrafish expressing in catecholaminergic neurons either membrane-anchored GFP to track fibers, or a Synaptophysin-GFP fusion to visualize putative synapses. We applied the CLARITY method to 6 days old whole zebrafish larvae to stain and analyze dopaminergic projections by confocal microscopy. We found that all lateral line neuromasts receive direct innervation by posterior tubercular dopaminergic neurons, and tracked these projections in detail. In addition, we found dopaminergic fibers projecting to the anterior and posterior lateral line ganglia, and extensive central dopaminergic arborizations around the terminal projection field of the lateral line afferent neurons in the hindbrain medial octavolateralis nucleus (MON). Therefore, dopaminergic innervation may affect lateral line sense information at different processing stages. Additional dopaminergic fibers innervate the trigeminal ganglion, and we observed fine catecholaminergic fibers in the skin with arborization patterns similar to free sensory nerve endings. We also detected potentially dopaminergic fibers innervating inner ear sensory epithelia. Therefore, the diencephalospinal A11-type dopaminergic system may broadly modulate peripheral senses. We also briefly report peripheral sympathetic catecholaminergic projections labeled in our experiments, and their innervation of the developing intestine, swim bladder and abdominal organs.